Dissociation and Brain Rhythms: Pitfalls and Promises - Grent-'t-Jong, Tineke; Melloni, Lucia; Uhlhaas, Peter J. (Frontiers in Psychiatry, 2021)
Recently, Vesuna and colleagues (Nature. 2020;586:87-94) proposed a novel circuit mechanism underlying dissociative states using optogenetics and pharmacology in mice in combination with intracranial recordings and electrical stimulation in an epilepsy patient. Specifically, the authors identified a posteromedial cortical delta-rhythm that underlies states of dissociation. In the following, we would like to critically review these findings in the context of the human literature on dissociation as well as highlight the challenges in translational neuroscience to link complex behavioral phenotypes in psychiatric syndromes to circumscribed circuit mechanisms.